Priority of competencies in the professional activities of general practitioners (family doctors) - O. M. Drapkina; S. Yu. Astanina; R. N. Shepel; O. Yu. Kuznetsova; T. V. Samoilov; D. V. Osipova; N. S. Alekseeva; I. V. Bakhareva; T. V. Bolotnova; M. E. Balashova; V. P. Buryakova; A. V. Vinogradov; et al. (Кардиоваскулярная терапия и профилактика)
The functional responsibilities of general practitioners (family doctors) (GPs) have changed significantly over the past decade. The number of GP functions has expanded. Despite the increasingly complex professional activities of GPs, there is no scientific evidence for the qualification characteristics of GPs expressed in knowledge, skills, abilities, and competencies in the theory and practice in training. In this regard, a study was conducted to determine the priority of GP competencies that make up the qualification characteristics of a specialist. Aim. To analyze, generalize and rationale the research results, as well as to develop preliminary guidelines for GP training. Material and methods. The information base for the study was the results of ranking competencies according to their importance in the professional activities of GPs in Russia. It was obtained during the ascertaining experiment, implemented using the Delphi method as a method of expert assessment and strategic planning of training specialists. Conclusion. The analysis of competencies developed and agreed upon by experts showed its compliance with the job functions of GPs, the requirements of the Federal State Educational Standard for the General Medical Practice (Family Medicine) and the WONCA guidelines. A summary of the study results to determine the priority of competence in GP activities showed the following: — all competencies (25) were defined as necessary and constitutive of GP qualification; — 21 competencies were considered significant and highly significant for GPs; — 4 competencies were considered as of moderate significance and below moderate significance. The analysis of the priority of competences revealed insufficient methodological support for GP training in accordance with the social order. The results obtained showed the need to continue the study within the project "Quality Management of Training of General Practitioners (Family Doctors)".